A new irregular monoterpene acetate along with eight known compounds with antifungal potential from the aerial parts of Artemisia incisa Pamp (Asteraceae). Issue 4 (16th February 2017) - Rashid, Mamoon Ur; Alamzeb, Muhammad; Ali, Saqib; Shah, Zafar Ali; Naz, Ishrat; Khan, Ashfaq Ahmad; Semaan, Dima; Khan, Mohammad Rafiullah
Abstract: A new compound named as santolinylol-3-acetate (4-(2-hydroxypropan-2-yl)-2-methylhexa-1, 5-dien-3-yl acetate) (3 ), along with seven known compounds; linoleic acid (1 ), benzoic acid (2 ), santolinylol (4 ), ethyl-( E )- p -hydroxy cinnamate (5 ), scopoletin (6 ), esculetin (7 ) isofraxidin (8 ) and eupatorin (9 ), were isolated from the aerial parts (ethanolic extract) of endangered species: Artemisia incisa Pamp (Asteraceae). The compounds' structures were determined through modern spectroscopic techniques, and comparison of data (physicochemical constants) with the literature. The relative stereochemistry of santolinylol-3-acetate (3 ) was determined by comparing its data of NOESY, and specific rotation with its diol analogue; santolinylol (4 ), isolated from the same plant; A. incisa . The results of the antifungal activity showed that coumarins are as whole less active compounds. Compounds3 (25 and 300 μg/mL), and4 (12.5 and 300 μg/mL), showed good activities against Candida albicans, and Aspergillus flavus, respectively, which justifies A. incisa as a traditional medicine for curing the said fungal infections. Abstract : Irregular monoterpene activity against Candida albicans infection.